Comparison between the four-kallikrein panel and Prostate Health Index (PHI) for predicting prostate cancer - Nordström, Tobias (Eur Urol, 2014)
BACKGROUND: The four-kallikrein panel and the Prostate Health Index (PHI) have been shown to improve prediction of prostate cancer compared to prostate-specific antigen (PSA). No comparison between the four-kallikrein panel and PHI has been presented. OBJECTIVE: To compare the four-kallikrein panel to PHI for predicting prostate cancer in an independent cohort. DESIGN, SETTING AND PARTICIPANTS: Participants were from a population-based cohort of PSA-tested men in Stockholm County. We included men (n=531) with PSA 3–15 ng/ml undergoing first-time prostate biopsy during 2010–2012. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Models were fitted to case status. We computed calibration curves, the area under the receiver-operating characteristics curve (AUC), decision curves, and percent saved biopsies. RESULTS AND LIMITATIONS: The four-kallikrein panel showed AUCs of 69.0 when predicting any-grade prostate cancer and 71.8 when predicting high-grade cancer (≥Gleason 7). Similar values were found for PHI: 70.4 and 71.1, respectively. Both models had higher AUC than a base model with PSA and age (p<0.0001 for both); differences between models were not significant. Sensitivity analyses including men with any PSA or a previous biopsy did not materially affect our findings. Using 10% predicted risk of high-grade prostate cancer by the four- kallikrein panel or PHI=39 as cutoff for biopsy saves 29% of performed biopsies to the cost of delayed diagnosis for 10% of the men with high-grade cancers. Both models showed limited net benefit in decision analysis. The main study limitation was lack of digital rectal examination data and biopsy decision being based on PSA information. CONCLUSIONS: The four-kallikrein panel and PHI similarly improved discrimination when predicting prostate cancer and high-grade prostate cancer. Both are simple blood tests that can reduce the number of unnecessary biopsies compared to screening with total PSA, representing an important new option to reduce harm.